2020
DOI: 10.1093/europace/euaa036
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of catheter ablation in patients with atrial fibrillation and heart failure

Abstract: Aims Randomized trials suggest reductions in all-cause mortality and heart failure (HF) rehospitalizations with catheter ablation (CA) in patients with atrial fibrillation (AF) and HF. Whether these results can be replicated in a real-world population with long-term follow-up or varies over time is unknown. We sought to evaluate the long-term effectiveness of CA in reducing the incidence of all-cause mortality, HF hospitalizations, stroke, and major bleeding in AF–HF patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
2
12
0
2
Order By: Relevance
“…Based on a recent well‐conducted observational study of catheter ablation in patients with AF and HF, the duration of effectiveness for CA on mortality and HF requiring hospitalization was assumed to be 3 years. 26 This is similar to the median follow‐up duration of CASTLE‐AF, which was 38 months. 14 …”
Section: Methodssupporting
confidence: 75%
“…Based on a recent well‐conducted observational study of catheter ablation in patients with AF and HF, the duration of effectiveness for CA on mortality and HF requiring hospitalization was assumed to be 3 years. 26 This is similar to the median follow‐up duration of CASTLE‐AF, which was 38 months. 14 …”
Section: Methodssupporting
confidence: 75%
“…645 A recent observational study showed that catheter ablation was associated with a long-term reduction in all-cause mortality and HF rehospitalizations. 646 There are no data showing a mortality benefit in patients with HF and preserved EF. The large multicentre Canadian randomized ablation-based Randomized Ablation-Based Atrial Fibrillation Rhythm Control vs Rate Control Trial in Patients With Heart Failure and High Burden Atrial Fibrillation (RAFT-AF) study has closed enrollment and is due to report later this year (NCT01420393).…”
Section: Candidates For Af Ablationmentioning
confidence: 99%
“…In 2020, Samuel et al provided a study [23] on catheter ablation in patients with HF and AF in a real-world setting with long-term follow-up within a Canadian population. Among 101,933 AF-HF patients, 451 (0.44%) underwent catheter ablation and were matched to 899 controls.…”
Section: Scientific Evidence Concerning Af Ablation In Hf Patientsmentioning
confidence: 99%